Quality calls - Pitcher, Fiona (London : BBC Training Videos, 1991)
The video looks at three Key Areas which need to be examined if the quality of telephone calls is to be improved, whether those calls are incoming or outgoing. Key area one: Quality Barriers, Key area two: Quality Basics, Key area three: Quality Builders
Writer, Mark Burton, Steve Punt, Fiona Pitcher
Keywords: Telephone etiquette; Telephone